Bilateral current account rebalancing in the EMU: The link between Germany and the eurozone peripheral countries - Georg Dettmann; Jochen Möbert; Christian Weistroffer (Intereconomics, 2012)
Some current account rebalancing within EMU is currently in progress. Following the financial crisis, German current account surpluses with Italy, Spain, Portugal and Greece have decreased. The following article shows that rebalancing has been achieved mainly at the expense of domestic demand in these countries. Moreover, although all four peripheral countries have achieved some rebalancing of their current accounts vis-à-vis Germany, the path of adjustment differs.
Keywords: 330; Zahlungsbilanzungleichgewicht; Leistungsbilanz; Wirtschaftliche Anpassung; Deutschland; Italien; Spanien; Portugal; Griechenland